Peran Kepuasan Pelanggan Dalam Memediasi Pengaruh Kualitas Produk Terhadap Loyalitas Pelanggan - Desy Dharmawati; Yoyok Cahyono; Dasa Rahardjo Soesanto; Popong Suryani (LPPM Universitas Pramita Indonesia, 2022)
This study aims to analyze the effect of product quality on customer loyalty either directly or through mediation of customer satisfaction. Causality design is used to determine the causal relationship between research variables with a quantitative research approach. Purposive sampling technique was used to determine the research sample in order to obtain as many as 110 Renault customers in PT Maxindo Mobil Indonesia BSD Tangerang. Data analysis was carried out using path analysis with SPSS version 26 program. The results showed that product quality directly had a positive and significant effect on customer satisfaction and customer loyalty, customer satisfaction could also play an intermediary variable so that product quality variables indirectly had a positive and significant influence. to customer loyalty.